Enhancing Secondary School Students ‘s Speaking Skill Through Picture-Based Storytelling Technique - Asis, Abdul (SENTRI: Jurnal Riset Ilmiah, 2025)
Abstract: Speaking is one of the essential skill in learning English, however Many students find difficulties in speaking English. They cannot speak well because of linguistic reasons such as their lack of vocabulary, pronunciation, and grammar knowledge. This study aimed to improve students’ speaking skill trough picture-based story-telling technique of second grade students of MA Nurul Huda Banyuates. This study employed classroom action research that was implemented on XI integrated students of Science and Religious Class consisting of 12Tstudents. The research was conducted in a cycle process starting from planning, implementation, observation, and reflection. In this study, the researcher used observation checklist, field note, and questionnaire to take the information of the students’ activities in the classroom, and an oral test with using an assessment rubric was design by the researcher based on the instructional material to know the students’ speaking improvement. The finding of this study showed that the use of picture-based story-telling technique that had been implemented by the researcher was effective in improving students’ speaking skill. It revealed that the students’ mean score of the post test was 71.32 in which 80% of the students got score ≥ 70. Besides improving students’ speaking ability, picture-based story-telling technique was proven to have stimulated the students’ enthusiasm, activeness, and fun during teaching and learning process.